A day in court [ young people and the criminal justice process - Carrel, Oliver; Harding, Ben (Video Education Australasia, 2006)
What constitutes a crime? When a person commits a crime, what happens to them? What rights do they - and the police - have? This program provides the answer to these questions with a brief overview of various types of crimes, followed by a detailed look at the magistrates court process through the eyes of young first-time offender, issues such as legal advice and types of sentences are also covered